PENYAKIT FISIK DAN LINGKUNGAN MEMPENGARUHI INSOMNIA LANSIA - Sofia Februanti; Dudi Hartono; Ai Cahyati (Quality : Jurnal Kesehatan, 2019)
Abstract: Physical and environmental diseases affect elderly insomnia. Sleep needs are basic human needs, including elderly. However, many elderly people have difficulty sleeping (insomnia). The purpose of this study was to determine the relationship of physical illness and environmental problems to insomnia experienced by the elderly. Research design using cross sectional Sampling with purposive sampling technique, with a total of 34 people. Data analysis using univariate and bivariate. The results showed that there was a relationship between physical illness and environmental problems with elderly insomnia. Keywords: elderly insomnia, environmental problems, physical illness